Mentoring, training and financing as drivers of entrepreneurial performance: Empirical evidence from the Fez-Meknes region, Morocco, using PLS-SEM - DIRI, Khalid; Slaoui, Samira (Edelweiss Applied Science and Technology, 2026)
Entrepreneurial support should be viewed not only as a strategic lever for development but also as a mechanism for business consolidation and long-term survival. This research presents the results of an empirical study examining the contribution of support structures to the performance of 150 entrepreneurs in the Fez-Meknes region of Morocco. The study is structured around four key dimensions: mentoring, financing, training, and networking, drawing on a theoretical framework that integrates resource-based theory [1, 2], human capital [3], social capital [4, 5], and organisational ecology [6, 7]. Using a quantitative approach based on a structured Likert-scale questionnaire, data were analyzed through a two-stage methodology combining principal component analysis (PCA) and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that mentoring (β=0.264, p<0.01), training (β=0.314, p<0.01), and access to finance (β=0.251, p<0.01) have a significant positive impact on business performance (R²=0.769), whilst networking shows no significant effect. These findings highlight the importance of contextually aligned, sector-specific support and suggest that policymakers should prioritize tailored mentoring, targeted training programs, and improved financial access mechanisms to enhance entrepreneurial performance in the Maghreb region.